MUHAMMADIYAH DA'WAH MOVEMENT EMPOWERMENT THROUGH THE ECONOMIC AND SOCIAL ORPHANS ORPHAN IN THE LAMPUNG PROVINCE - Anas Habibi Ritonga; Nashor Nashor; Damrah Khair; Hasan Mukmin (Postgraduate State Islamic Institute (IAIN) Metro, 2019)
The purpose of this study is; First, to find out and analyze in depth the Program of the Muhammadiyah Movement in the Lampung Region through the Socio-Economic Empowerment of Orphans. Second, to find out and analyze in depth the effectiveness of the Muhammadiyah Da'wah Movement Pattern in the Lampung Region through the Socio-Economic Empowerment of Orphans. Third, to find out and analyze in depth the Evaluation of the Muhammadiyah Da'wah Movement in the Lampung Region through the Socio-Economic Empowerment of Orphans that has been going well. The approach used is descriptive qualitative with the phenomenology approach. Data collection techniques through; in-depth interviews, observations, and documentation studies. Then the validity test is performed, the data are analyzed in a way; 1) data reduction, 2) presentation data and 3) research conclusions. Research result; (1) The Muhammadiyah Da'wah Movement Program through the Socio-Economic Empowerment of Orphans in Lampung Province, there are three namely; a. Childcare Social Home Program, b. Family Care Program and c. Family Care Program (Family Benefits). (2) The pattern of the Muhammadiyah Da'wah Movement through the Socio-Economic Empowerment of Orphans there are two patterns or forms, namely; Training and Assistance or Internship (3) Evaluation of the Muhammadiyah Da'wah Movement in the Lampung Region through the Socio-Economic Empowerment of Orphans is successful by seeing an increase in the level of awareness, knowledge and skills of orphans who have been given assistance , apprenticeships and trainings.